2008
DOI: 10.1080/15427951.2008.10129300
|View full text |Cite
|
Sign up to set email alerts
|

A Singular Perturbation Approach for Choosing the PageRank Damping Factor

Abstract: The choice of the PageRank damping factor is not evident. The Google's choice for the value c = 0.85 was a compromise between the true reflection of the Web structure and numerical efficiency. However, the Markov random walk on the original Web Graph does not reflect the importance of the pages because it absorbs in dead ends. Thus, the damping factor is needed not only for speeding up the computations but also for establishing a fair ranking of pages. In this paper, we propose new criteria for choosing the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…The reason for this is that at higher values for α the peripheral parts of the citation network receive too much weight relative the more important central ones, which as a consequence become underrated (cf. Boldi et al, 2005;Avrachenko et al, 2008). of α close to 0.5.…”
Section: Indicatorsmentioning
confidence: 99%
“…The reason for this is that at higher values for α the peripheral parts of the citation network receive too much weight relative the more important central ones, which as a consequence become underrated (cf. Boldi et al, 2005;Avrachenko et al, 2008). of α close to 0.5.…”
Section: Indicatorsmentioning
confidence: 99%
“…(7) [8,25]: (7) Where is the teleportation matrix of , controls priority given to the hyperlink structure over artificial teleportation matrix . Many researchers state that the value of damping factor affect the convergence rate of PageRank Power method [11,12,14,18,19]. We have performed an experiment to observe the impact of damping factor on the convergence rate of PageRank algorithm, and ordering of web pages displayed on web search engine on various datasets by using following Eq.…”
Section: Effect Of Damping Factor On Pagerank Algorithmmentioning
confidence: 99%
“…In this experiment we have taken, only top 25 web pages return by PageRank method because SERP (Search engine result pages) contains almost 20 to 30 web pages in their first result page that are more relevant to the web user, and on average 90% users do not go beyond the first result page for any particular query [9,11]. If any web page indexed in the top 25 position for but cannot get position in top 25 for , then we have taken a parameter to show that whether page is indexed in top 25 or not, parameter is defined as follows:…”
Section: Damping Factor Value Versus Convergence Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers take α = 0.85 [6]. Recently, Avrachenkov et al suggested choosing α = 1/2 [7]. Their suggestion follows from graph theoretic properties of the PageRank solution vector as a function of α.…”
Section: Introductionmentioning
confidence: 99%